Butterfly richness and abundance in flower strips and field margins: the role of local habitat quality and landscape context. Issue 5 (May 2019) - Wix, Nana; Reich, Michael; Schaarschmidt, Frank
Abstract: Flower strips, which are created on arable land by sowing species-rich seed mixtures, are considered to have a high potential to counteract species decline of butterflies in the agricultural landscape. However, it remains largely unexplored how various factors (design, habitat quality, landscape context) interact to determine the occurrence of butterflies in flower strips. Therefore, butterflies were surveyed in 15 flower strips differing in age (first and second growing season). Flower strips were compared with 15 field margins, which were adjacent to arable land and were dominated by grasses. The field studies were conducted during two summers (2013, 2014) in Lower Saxony (Germany). Additionally, based on a literature study, 17 environmental variables likely to be decisive for the occurrence of butterflies were identified and recorded during these field studies or analyzed in GIS. Supported by a PCA, 8 environmental variables for flower strips and 7 for field margins, were selected and included in linear mixed-effects models in order to calculate their effect on butterflies. We documented 19 butterfly species and 1, 394 individuals in the flower strips and 13 species and 401 individuals in the field margins. The number of flowering plant species was the key factor for the occurrence of butterflies - both in flower strips and field margins. The diversity of the surrounding landscape (Shannon-Index H) had an additional significant influence on butterflies in flower strips, with more species and individuals being observed on areas with a lower Shannon-Index. Number of flowering plant species is the key driver of butterfly diversity and abundance, which improves the habitat quality of flower strips in agricultural landscapes. In order to promote butterflies optimally, flower strips must have a good supply of flowers even over several years. This requires careful design and management, as flower supply often decreases with increasing age of the flower strips. The study indicates that flower strips have a particularly high effect in structurally simple landscapes.